2006
DOI: 10.1021/cm0613410
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Nanometer-Scale Mixing in Phosphate-Glass/Polyamide-6 Hybrids by 1H−31P NMR

Abstract: The size of phosphate-glass (Pglass) particles dispersed in a polyamide-6 (PA6) matrix by melt blending has been characterized by 1 H-31 P solid-state nuclear magnetic resonance (NMR). 1 H spin diffusion from ∼75% of the 1 H in the glass to the polyamide is observed within 50 ms, indicating proximity on a 30 nm scale. Fast dephasing of a quarter of the 31 P magnetization by dipolar couplings to polyamide protons in 31 P{ 1 H} heteronuclear recoupling with dephasing by strong homonuclear interactions of protons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 25 publications
8
26
0
Order By: Relevance
“…Therefore, the segmental motions are highly constrained by the increase in the crystalline regime of the hybrid. This hypothesis just mentioned is consistent with previously reported 1 He 31 P solid state and 31 P [43] heteronuclear recoupling with dephasing by strong homonuclear interactions of protons' (HARDSHIP) NMR data on the Pglass/polyamide 6 hybrid [43]. The NMR data revealed that 1 H spin diffusion from 75% of the 1 H in the glass to the polyamide is within 50 ms, indicating proximity on a 30 nm scale.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the segmental motions are highly constrained by the increase in the crystalline regime of the hybrid. This hypothesis just mentioned is consistent with previously reported 1 He 31 P solid state and 31 P [43] heteronuclear recoupling with dephasing by strong homonuclear interactions of protons' (HARDSHIP) NMR data on the Pglass/polyamide 6 hybrid [43]. The NMR data revealed that 1 H spin diffusion from 75% of the 1 H in the glass to the polyamide is within 50 ms, indicating proximity on a 30 nm scale.…”
Section: Resultssupporting
confidence: 91%
“…The decrease of D3 may be attributed to possible Pglass-induced crystallinity and formation of new crystal modification in the polyamide 6 as confirmed by NMR data that will be reported in the second paper to be published elsewhere. This crystal modification is due to the very fine morphology of the dispersed Pglass in the polyamide 6 matrix, which can act as a nucleating agent for the crystallization process as discussed later [43]. Therefore, the segmental motions are highly constrained by the increase in the crystalline regime of the hybrid.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, because of the partial miscibility of the constituent phases, the local properties can vary in a nontrivial manner across the interfaces. 3,22,29 It is precisely a combination of all these factors that brings about the interesting and advantageous properties of the present hybrids. But it is also the same factors that make it so difficult to develop accurate theoretical equations for predicting the properties of the hybrids.…”
Section: Tensile Propertiesmentioning
confidence: 98%
“…As part of our long-range research program in this field, modern solid-state nuclear magnetic resonance (NMR) methods are being used to provide useful information on composition, nanometer-scale mixing, and dynamics in the hybrid systems; the results obtained will be reported elsewhere. 22 The favorable chemical interactions between the hybrid components and their mixing in the liquid state will enhance the mechanical properties of the Pglass/polyamide 12 hybrids for a number of applications, making the present hybrid system useful model systems for exploring feasibility of new processing routes for driving organic polymers and inorganic phosphate glasses to selfassemble into useful hybrid materials.…”
Section: Introductionmentioning
confidence: 99%
“…This tends to suggest that the POSS that is chemically linked to the hard segments of the PU improves the compatibility between hard and soft segments. This phenomenon is ascribed to the large surface area of nano-particles that create the large interaction domains with the PU hard and soft segments [42][43][44]. Figure 3 shows the XRD patterns of APS (the POSS), PU0 and PU2 to PU10 (the PU/POSS hybrids films).…”
Section: Resultsmentioning
confidence: 99%